Synergistically Directed Assembly of Aromatic Stacks Based Metal‐Organic Frameworks by Donor‐Acceptor and Coordination Interactions1. Issue 9 (8th July 2019) - Wang, Xi; Zhang, Ying; Chang, Ze; Huang, Hui; Liu, Xiao‐Ting; Xu, Jialiang; Bu, Xian‐He
Summary of main observation and conclusion: A synergistically directed assembly approach to distinctive metal‐organic frameworks utilizing both donor‐acceptor (D‐A) interaction from aromatic systems and coordination interactions is presented. Based on such an approach, the coronene‐tpt (tpt = 2, 4, 6‐tri(4‐pyridyl)‐1, 3, 5‐triazine) stacks basedcoronene‐MOF‐1 —4 have been successfully fabricated. Their structural discrepancies with coronene‐ absent control products, 1′ —4′, illustrate clearly the significance of coronene‐tpt based D‐A interactions in these architectures. All these coronene‐MOFs contain varied coronene‐tpt stacks as organic secondary building blocks (SBUs), which are closely interrelated with the coordination based framework structures. Moreover, porouscoronene‐MOF‐1 and‐2 exhibit high physicochemical stability and significant light hydrocarbons storage and separation performances. Abstract : The synergistically directed assembly strategy toward donor‐acceptor stacks based frameworks is proposed on the basis of supramolecular donor‐acceptor and coordination interactions. As a proof of concept, four novel coronene‐MOFs were prepared by the deliberate introduction of coronene (donor) into tpt (acceptor) involved coordination assemblies. The porouscoronene‐MOF‐1 and‐2 reveal high physiochemical stability and considerable hydrocarbons storage and separation performances.